Research on the Impact of Big Data Management on Enterprise Agility - Liu, Zhen; Abbas Ali, Dhakir (International Journal of Global Economics and Management, 2024)
This study explores the impact of big data management on enterprise agility. With the rapid development of information technology, the application of big data technologies in corporate management is increasingly widespread. Enterprise agility, crucial for responding to market changes and competitive pressures, is highly prioritized by businesses. Through literature review, case analysis, and empirical studies, this research examines how big data management enhances an enterprise's capability for rapid decision-making, flexible adjustment, and continuous innovation. The study finds that effective big data management not only improves decision efficiency but also strengthens the enterprise's adaptability to dynamic market changes. Finally, the paper proposes future research directions and provides guidance for corporate practice.